2015
DOI: 10.14737/journal.jahp/2015/3.4.99.103
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Profile of Staphylococcus aureus Isolates Recovered from Various Animal Species

Abstract: Staphylococcus aureus, a normal flora of human and animals is recognized as an opportunistic pathogen that cause several infections. In present study, eighty S. aureus isolates were recovered from different animals such as sheep, goat, buffalo, camel, horse, cattle, dog and human. These isolates were exposed to in vitro antibiotic sensitivity test using eleven antimicrobial agents which included ampicillin (10µg), amikacin (30µg), chloramphenicol (30µg), sulfanilamide (30µg), erythromycin (15µg), gentamicin (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Results of antibiotic susceptibility showed sensitive to Gentamicin, ciprofloxacin, sulfamethoxazole-trimethoprim and cephalothin while resistance to erythromycin, tetracycline, ampicillin and penicillin (Table 1). These results are almost in agreement to recent studies (Habib et al, 2015).…”
Section: Resultssupporting
confidence: 94%
“…Results of antibiotic susceptibility showed sensitive to Gentamicin, ciprofloxacin, sulfamethoxazole-trimethoprim and cephalothin while resistance to erythromycin, tetracycline, ampicillin and penicillin (Table 1). These results are almost in agreement to recent studies (Habib et al, 2015).…”
Section: Resultssupporting
confidence: 94%
“…The spread plate method was used to isolate and count Staphylococcus species grown on Salt Mannitol Agar [ 26 ]. Dilutions of the sample, ranging from 10 −1 to 10 −4 , by mixing 10 g of the sample with 90 ml of sterilized peptone water and pulsifying for 15 s. 1 ml portion from each dilution was dispensed onto Petri dishes filled with prepared Salt Mannitol Agar (SMA).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study have reported the multidrug resistant Staphylococcus aureus as a causative agent of septic arthritis in poultry birds (Nazia et al, 2015). A recent study has demonstrated the host-related differences in susceptibility levels of Staphylococcus aureus isolates from different farm animals, thus indicated a host-microbe interaction and probable role of host in development of antimicrobial resistance in Staphylococcus aureus organisms (Habib et al, 2015).…”
Section: Staphylococcus Aureus Isolatesmentioning
confidence: 99%